Modeling of an Electromagnetic Cannon using ATP-EMTP and ATPDraw - José Manuel Aller; Juan José Cordero Cantos; Pedro José León Rojas; Jhonny Rengifo (Ingenius: Revista de Ciencia y Tecnología)
This study presents a computational model of an electromagnetic cannon developed using the ATP/EMTP simulation tool and its graphical interface, ATPDraw. The system features a cylindrical metallic armature that traverses multiple stages of circular coils. Employing the Voltage Behind Reactance (VBR) methodology, each coil is modeled as a dynamic equivalent circuit comprising a resistance, an inductance, and an electromotive force source. The model parameters are dynamically updated at each simulation time step based on the armature’s motion. The coils are energized by pre-charged capacitors and connected through thyristors, which are triggered at specific positions of the moving armature. The model’s validity is corroborated by experimental data reported in the literature, confirming the accuracy and robustness of the proposed approach. In addition to supporting the design of electromagnetic cannons, this work provides a methodological foundation for future research and practical applications in this domain.